Coexistent Mitral Stenosis and left Circumflex Coronary Artery to left Atrial Fistula in a Patient with Severe Pulmonary Hypertension - Shi,Yaming (2021)
Abstract Coronary artery to left atrial fistula is rare in patients with mitral stenosis. We report an interesting case of a patient with concomitant mitral valve stenosis and coronary fistulae, originating from the left circumflex artery and drained into the left atrium with two terminal orifices.